The combination of plasmid interleukin-12 with a single DNA vaccine is more effective than Mycobacterium bovis (bacille Calmette–Guèrin) in protecting against systemic Mycobacterim avium infection - Martin, Ela (Blackwell Publishing Inc, 2003)
Sub-unit vaccines utilizing purified mycobacterial proteins or DNA vaccines induce partial protection against mycobacterial infections. For example, immunization with DNA vaccines expressing the gene for the immunodominant 35 000 MW protein, common to Mycobacterium avium and Mycobacterium leprae but absent from the Mycobacterium tuberculosis complex, conferred significant protection against infection with either virulent M. avium or M. leprae in mice. However, the level of protection was equivalent to that obtained with the viable, attenuated vaccine, Mycobacterium bovis, bacille Calmette–Guèrin (BCG). The cytokine, interleukin (IL)-12, is essential for priming naïve CD4(+) T lymphocytes to differentiate into interferon-γ (IFN-γ)-secreting T cells. We have used a novel self-splicing vector expressing both chains of murine IL-12 to determine if plasmid IL-12 would increase the efficacy of a vaccine expressing the M. avium 35 000 MW protein (DNA-Av35). Co-immunization with p2AIL-12 and DNA-Av35 led to a significant increase in the number of antigen-specific IFN-γ secreting cells and total amount of IFN-γ released, but a concomitant fall in the antibody response to the 35 000 MW protein. This pattern of response was associated with enhanced clearance of M. avium from the liver and spleen of coimmunized mice, and was significantly more effective than BCG or DNA-Av35. alone. Following M. avium challenge there was significant increase in the expansion of the 35 000 MW antigen-reactive T cells in the coimmunized mice. Therefore, plasmid-delivered IL-12 acts as an effective adjuvant to increase the protective efficacy of a single DNA vaccine against M. avium infection above that achieved by BCG, and this strategy may improve the efficacy of subunit vaccines against M. leprae and M. tuberculosis.